Preserving Zibo cultural heritage exploring the symbolism, visual identity, and conservations efforts of the fish motif pattern design - Abdul Rahman, Ahmad Rizal; Shao, Nini; Alli, Hassan; R.A. Effendi, Raja Ahmad Azmeer (Heranca, 2024)
As the intangible cultural heritage of Shandong Province, Zibo fish plate is deeply rooted in the rich soil of Chinese traditional culture with rich folk culture connotation and symbolic significance. For thousands of years, the local folk culture and art condensed and expressed in the fish motif pattern decoration of Zibo fish plate, making Zibo fish plate unique in aesthetic performance of a mellow and rough charm. As an artistic work with national characteristics and the spirit of the times gradually formed in the evolution of society and history, this paper will start with the development process and characteristics of Zibo fish plate, in-depth analysis of the symbolic meaning and expression of Zibo fish motif pattern. In view of the current difficulties facing the inheritance of fish mother patterns in Zibo, the corresponding solutions are put forward. Relevant research has deeply revealed the relationship between the Zibo fish motif pattern and Chinese traditional culture and has solid theoretical and historical research value.